Treatment of angular cheilitis: A narrative review and authors' clinical experience. (11th September 2019) - Cabras, Marco; Gambino, Alessio; Broccoletti, Roberto; Lodi, Giovanni; Arduino, Paolo G.
Abstract: Angular cheilitis (AC) is a clinical entity first described in the XIX century, characterized by erythema, rhagades, ulcerations, and crusting of one or both lip commissures and perilabial skin, responsible of an unpleasant and painful discomfort. Aim of this manuscript was to examine and evaluate the therapeutic options actually available for AC. Despite antifungals being the first‐line treatment for most of clinicians, very limited scientific evidence supports their reliability, with just two RCTs published between the 70's and the 80's. Furthermore, alternative topical treatments, various techniques of occlusal vertical dimension restoration, B‐vitamin supplementation, anti‐drooling prosthetic device, and photodynamic therapy have been experimented and proposed, mostly in the form of case reports or case series on a small number of individuals. Our group found in 1% isoconazole nitrate (ISN) and 0.1% diflucortolone valerate (DFV) ointment the most consistent AC treatment, due to the broad spectrum of ISN against many species of dermatohpytes and bacteria, and the anti‐inflammatory properties displayed by DFV. However, further and well‐designed trials on larger samples of patients are needed to assess the differential profile of consistency of the treatments outlined in literature and claimed by the authors of this paper.